2016
DOI: 10.1186/s40824-016-0073-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular weight of hyaluronic acid (HA) on viscoelasticity and particle texturing feel of HA dermal biphasic fillers

Abstract: BackgroundHyaluronic acid (HA) dermal biphasic fillers are synthesized for their efficacy in correcting aesthetic defects such as wrinkles, scars and facial contouring defects. The fillers consist of crosslinked HA microspheres suspended in a noncrosslinked HA. To extend the duration of HAs within the dermis and obtain the particle texturing feel, HAs are crosslinked to obtain the suitable mechanical properties.ResultsHyaluronic acid (HA) dermal biphasic fillers are prepared by mixing the crosslinked HA micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…The wrinkle‐improving effect was the major difference in the mean depth of biggest wrinkles improvement between 15.69% in the Ad‐HMN group and 0.41% in the Ad‐LMN group after 8 weeks of use. These results indicated that the Ad‐HMN group efficiently transfers high molecular weight HA into the skin, and the Ad‐HMN group has more wrinkle improvement to the Ad‐LMN group due to the high degree of swelling of the high molecular weight HA relative to the low molecular weight HA of Ad‐LMN group [21,22]. These results indicated the successful manufacture and application of microneedle cosmetics using high molecular weight HA without the conventional HA synthesized by cross‐linking.…”
Section: Resultsmentioning
confidence: 99%
“…The wrinkle‐improving effect was the major difference in the mean depth of biggest wrinkles improvement between 15.69% in the Ad‐HMN group and 0.41% in the Ad‐LMN group after 8 weeks of use. These results indicated that the Ad‐HMN group efficiently transfers high molecular weight HA into the skin, and the Ad‐HMN group has more wrinkle improvement to the Ad‐LMN group due to the high degree of swelling of the high molecular weight HA relative to the low molecular weight HA of Ad‐LMN group [21,22]. These results indicated the successful manufacture and application of microneedle cosmetics using high molecular weight HA without the conventional HA synthesized by cross‐linking.…”
Section: Resultsmentioning
confidence: 99%
“…The pore size was then determined by using the optical microscope equipped with the iSolution Lite image software. [13][14][15][16][17][18][19][20][21] Compressive strength of the irradiated PVA/ CMC hydrogels was examined by using an Instron 5564 with a crosshead speed of 10 mm/min. The specimen with a diameter of 15 mm and a thickness of 5 mm was fabricated and the strength was determined at a point where the specimen thickness decreased by 50%.…”
Section: Hydrogel Synthesismentioning
confidence: 99%
“…The extract test method was conducted on the irradiated PVA/CMC/PEG hydrogels to evaluate the potential of cytotoxicity according to the International Organization for Standardization (ISO 10993-5). [13][14][15][16][17][18][19][20][21] The hydrogels were extracted aseptically in single strength minimum essential medium (1× MEM, Dulbecco's modified Eagle's medium [Gibco, Paisley, United Kingdom] with 10% fetal bovine serum [Gibco, Paisley, United Kingdom] and 1% penicillin-streptomycin) with serum. The ratio of the hydrogels to the extraction vehicle was 0.1 g/ml (ISO 10993-12).…”
Section: Cytotoxicity and Cell Proliferationmentioning
confidence: 99%
See 2 more Smart Citations